ANALISIS PROFITABILITAS, UKURAN PERUSAHAAN DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Budiyono, Tri; Br. Purba, Neni Marlina (LPPM Universitas Putera Batam, 2021)
The purpose of this study is to analyze the effect of profitability, company size and sales growth on firm value in the Indonesia Stock Exchange. The total population in this study were 10 manufacturing companies in the pharmaceutical sub sector which were listed on the Indonesia Stock Exchange in 2015-2019. This study the sampling technique used a purposive sampling method so that 7 companies that met the criteria desired by the researcher were selected. The data used is secondary data obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id) and the Riau Islands representative IDX office in Batam City. The data used consists of documentation techniques. This study uses the SPSS version 25 program in processing data. The results of the t test are partially, profitability and firm size have a significant effect on firm value and sales growth has no significant effect on firm value. The results of the F test show that simultaneously profitability, company size and company sales growth have a significant effect on firm value.